Effects of Different Phosphorus Sources on the Yield and Yield Components of Forage Pea - Çomakli, Binali; Kaynar, Dilara (Ataturk Universitesi, 2023)
This experiment was conducted to evaluate the effects of two different doses (B0 or B1) of phosp horus-solubilizing bacteria (Bacillus megaterium M-3) inoculation, two different doses (0 or 3 t ha−1) of poultry manure, and three different doses (0, 50, and 100 kg P 2O5 ha−1) of commercially available phosphorus fertilizer on the dry matter yield, plant height, crude protein, neutral deter- gent fiber, and acid detergent fiber contents of forage pea in the irrigated condition of Erzurum between 2009 and 2010. While the effects of bacteria inoculation and poultry manure applica- tions on dry matter yield varied over the years, an increase was observed in dry matter yield with increasing doses of phosphorus fertilizer. In addition, considering the 2-year averages, the highest dry matter yield considering the 2-year averages was obtained with the application of bacteria, poultry manure, and phosphorus fertilization together. Therefore, in order to obtain the highest dry hay yield in Erzurum and similar ecological conditions with low and/or medium phosphorus content in the soil and irrigated, Bacillus megaterium inoculation and 3 t ha −1 poultry manure together with 100 kg ha−1 P2O5 application can be recommended.